Β-catenin tyrosine 654 phosphorylation increases Wnt signalling and intestinal tumorigenesis. Issue 9 (9th February 2011) - van Veelen, Wendy; Le, Ngoc H; Helvensteijn, Werner; Blonden, Lau; Theeuwes, Myrte; Bakker, Elvira R M; Franken, Patrick F; van Gurp, Léon; Meijlink, Frits; van der Valk, Martin A; Kuipers, Ernst J; Fodde, Riccardo; et al.
Abstract : Objective: Deregulation of the Wnt signalling pathway by mutations in the Apc or β - catenin genes underlies colorectal carcinogenesis. As a result, β -catenin stabilises, translocates to the nucleus, and activates gene transcription. Intestinal tumours show a heterogeneous pattern of nuclear β -catenin, with the highest levels observed at the invasion front. Activation of receptor tyrosine kinases in these tumour areas by growth factors expressed by surrounding stromal cells phosphorylate β -catenin at tyrosine residues, which is thought to increase β -catenin nuclear translocation and tumour invasiveness. This study investigates the relevance of β -catenin tyrosine phosphorylation for Wnt signalling and intestinal tumorigenesis in vivo. Design: A conditional knock-in mouse model was generated into which the phospho-mimicking Y654E modification in the endogenous β - catenin gene was introduced. Results: This study provided in vivo evidence that β -catenin E654 is characterised by reduced affinity for cadherins, increased signalling and strongly increased phosphorylation at serine 675 by protein kinase A (PKA). In addition, homozygosity for the β - catenin E654 targeted allele caused embryonic lethality, whereas heterozygosity predisposed to intestinal tumour development, and strongly enhanced Apc -driven intestinal tumour initiation associated with increased nuclear accumulation of β catenin. Surprisingly, the expression of β -catenin E654 did not affect histological grade or induce tumour invasiveness. Conclusions: A thus far unknown mechanism was uncovered in which Y654 phosphorylation of β -catenin facilitates additional phosphorylation at serine 675 by PKA. In addition, in contrast to the current belief that β -catenin Y654 phosphorylation increases tumour progression to a more invasive phenotype, these results show that it rather increases tumour initiation by enhancing Wnt signalling.